PATH-25. APPLICABILITY OF A NOMOGRAM INCLUDING CLINICAL AND MOLECULAR VARIABLES IN THE STRATIFICATION OF RISK GROUPS IN PEDIATRIC MEDULLOBLASTOMA. (11th November 2019) - Mançano, Bruna; Reis, Rui; Leal, Leticia; de Paula, Flavia; Almeida Jr, Carlos; Almeida, Gisele; Matushita, Marcus; Faustino, Fabio; Cavalcante, Carlos; Magalhães, Fernanda; Oliveira, Marco
Abstract: Medulloblastoma is the most common type of malignant brain tumor that occurs during childhood and adolescence. Currently, this pathology comprises at least four different molecular tumor subtypes (WNT, SHH, group 3 or C and group 4 or D) which have their own molecular characteristics, distinct clinical presentations and are associated with different survival rates. The purpose is to evaluate the applicability of a nomogram that includes clinical and molecular variables in pediatric medulloblastomas in the routine of the Hospital de Cancer de Barretos. The series l consists of 85 pediatric patients from 0 to 18 years old, diagnosed with medulloblastoma attended at the Hospital de Cancer de Barretos (HCB), from January 2000 to December 2017. The molecular subgroups will be performed using the Nanostring technique. This research intends to implement a nomogram that uses several variables known and involved in the treatment and prognosis of patients, this nomogram with multiple variables will show the clinical and molecular effect of each variable to predict disease-free survival and survival overall in 3 and 5 years. Thus, we will have the opportunity to analyze these characteristics in order to improve survival and reduce morbidity and consequently mortality during treatment for the different subgroups of medulloblastomas.